Study on recycling programs in Kuching - Farina, Unus (University Malaysia Sarawak, UNIMAS., 2006)
Nowadays, there is an increase of the generation of waste materials. This will diminish the life of landfills area. Thus, one of the possible solutions for this matter is by implementing recycling program which will eventually reduce the amount of waste materials. This study focuses on the method recycling program available in Kuching area. Through this method, the community will be able to recognize recyclable items.